Decreased Adrenomedullary Function in Infants With Classical Congenital Adrenal Hyperplasia - Kim, Mimi S. (Endocrine Society, 2014)
CONTEXT: Classical congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency can cause life-threatening adrenal crises as well as severe hypoglycemia, especially in very young children. Studies of CAH patients 4 years old or older have found abnormal morphology and function of the adrenal medulla and lower levels of epinephrine and glucose in response to stress than in controls. However, it is unknown whether such adrenomedullary abnormalities develop in utero and/or exist during the clinically high-risk period of infancy and early childhood. OBJECTIVE: The objective of the study was to characterize adrenomedullary function in infants with CAH by comparing their catecholamine levels with controls. DESIGN/SETTINGS: This was a prospective cross-sectional study in a pediatric tertiary care center. MAIN OUTCOME MEASURES: Plasma epinephrine and norepinephrine levels were measured by HPLC. RESULTS: Infants with CAH (n = 9, aged 9.6 ± 11.4 d) had significantly lower epinephrine levels than controls [n = 12, aged 7.2 ± 3.2 d: median 84 [(25th; 75th) 51; 87] vs 114.5 (86; 175.8) pg/mL, respectively (P = .02)]. Norepinephrine to epinephrine ratios were also significantly higher in CAH patients than controls (P = .01). The control infants had primary hypothyroidism, but pre- and posttreatment analyses revealed no confounding effects on catecholamine levels. CONCLUSIONS: This study demonstrates for the first time that infants with classical CAH due to 21-hydroxylase deficiency have significantly lower plasma epinephrine levels than controls, indicating that impaired adrenomedullary function may occur during fetal development and be present from birth. A longitudinal study of adrenomedullary function in CAH patients from infancy through early childhood is warranted.